Studi Literatur: Pendekatan Cognitive Behavior Therapy (CBT) untuk Mengatasi Post Traumatic Stress Disorder (PTSD) pada Korban Gempa Bumi: Array - Lusi Ramadhani; Yeni Karneli; Netrawati (Citra Dharma Cindekia, 2022)
The background of this article is the earthquake victims who experienced Post Traumatic Stress Disorder after the disaster. Cognitive Behavior Therapy (CBT) is a counseling approach that focuses on improving cognitive deviance due to events that harm him both physically and psychologically. This counseling will be directed at modifying the functions of thinking, feeling, and acting, by emphasizing the brain as an analyzer, decision maker, asking questions, acting, and deciding again.